Modelling the interaction of sustainable variables in Yellow River basin: a PVAR approach - Yan, Xiaohan; Chin, Lee; Abdul Samad, Abdul Rahim; Muhamad Senan, Mohamad Khair Afham (Human Resource Management Academic Research Society, 2024)
Economic development, environmental quality and residents’ health are significant topics in sustainability. The relationship between them can, to some extent, determine the potential for sustainable development in the region. The Yellow River basin (YRB) in China has an important strategic position of water conservation, ecological protection, and stability and unity of ethnic minorities for the whole China. Therefore, it is of great significance to study the relationship there. Using balanced panel data from 2014 to 2019, this paper selected carbon emissions intensity, gross domestic products per capita, and proportion of private health expenditure to consumption of nine provinces in the YRB as research variables, constructed a PVAR model, and analyzed and studied the interaction among them. The research shown that the three variables have close impulse and response relationship. The improvement in economic development and public health would stimulate carbon emissions. However, the intensity of carbon emissions increment will basically not affect the physical health of local residents, but might hinder economic development. In order to ensure the high-quality development of the YRB in China, the harmonious and coordinated development of the relationship among these sectors is essential.